Filtration of viral aerosols via a hybrid carbon nanotube active filter. (15th October 2021) - Issman, Liron; Graves, Brian; Terrones, Jeronimo; Hosmillo, Myra; Qiao, Rulan; Glerum, Michael; Yeshurun, Shuki; Pick, Martin; Goodfellow, Ian; Elliott, James; Boies, Adam
Abstract: Exposure to expired particles and droplets carrying infectious viruses is a primary transmission pathway for respiratory diseases. Removal of particles and droplets via filtration from a volume can drastically reduce the exposure to viruses, but viruses may remain active on filtration surfaces as potential resuspension or fomite risks. Here, we report the development of macroscopic carbon nanotube air filters synthesized using ultra-thin carbon nanotube electrically conductive membranes, mechanically supported by a porous polyester backing. Filtration efficiencies were measured up to 99.999%, while ultra-thin materials with low areal density (0.1 g m ─2 ) exhibited pressure drops comparable to commercial High-Efficiency Particulate Air (HEPA) filters. These electrically conductive filters are actively self-sanitized by thermal flashes via resistive heating to temperatures above 80 °C within seconds or less. Such temperatures were proven to achieve full deactivation of a betacoronavirus and an adeno-associated virus retained on filter surfaces. A filtration unit prototype equipped with a CNT filter module (∼1.2 m 2 ) was shown to achieve air purification of 99% of a room within 10 min at 26 air changes per hour. Graphical abstract: Image 1